Chromosome-Level Genome Assembly of Cyrtotrachelus buqueti and Mining of Its Specific Genes - Fu, Chun; Long, WenCong; Luo, ChaoBing; Nong, Xiong; Xiao, XiMeng; Liao, Hong; Li, YuanQiu; Chen, Ying; Yu, JiaXin; Cheng, SiXuan; Baloch, Saira; Yang, YaoJun (Frontiers in Ecology and Evolution, 2021)
Background: The most severe bamboo insect is the bamboo-snout beetle (Cyrtotrachelus buqueti). Bamboo is a perennial plant that has many life and economic importance. C. buqueti also plays a vital role in the deterioration of bamboo lignocellulose, in addition to causing damage. Results: A one paired-end (PE) library used for estimating the size of the C. buqueti genome was close to 600.92 Mb by k-mer analysis. Then, we developed nine 20-kb SMRTbell libraries for genome sequencing and got a total of 51.12 Gb of the original PacBio sequel readings. Furthermore, after filtering with a coverage depth of 85.06x, clean readings with a total of 48.71 Gb were obtained., The final size of C. buqueti genome is 633.85 Mb after assembly and measurement, and the contig N50 is 27.93 Mb. These results show that the assembly level of this genome is the highest in the assembly quality of all known insect genomes. The gene comprises roughly 630.86 Mb of the genome sequence (99.53%). 1063 conserved genes were collected at the genome assembly, comprising 99.72 % of the overall genes with 1066 by using the Benchmark Uniform Single-Copy Orthology (BUSCO). 63.78% of the C.buqueti genomes are repetitive, and 57.15% are repetitive with long-term elements. 12569 protein-coding genes were acquired after annotation, of which 96.18% were functionally annotated. The comparative genomic analysis results revealed that D. ponderosae was similar to C. buqueti. Conclusion: At the chromosome level, we have obtained a high-quality C. buqueti genome. This insect's genome assembly is more potent than that of other insects that have been documented. The C. buqueti genome contains useful tools, including host plant recognition, bamboo lignocellulose degradation, and defensive responses, to research the relationship between insects and bamboo.